Poultry waste effects on shallow groundwater quality in selected farms in Minna, North-Central Nigeria - Adeoye, Peter Aderemi; Che Man, Hasfalina; Mohd Soom, Mohd Amin; Mohamed, Thamer Ahmed; Akinbile, Christopher Oluwakunmi (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Provision of adequate and potable water for both rural and urban dwellers should be seen as a necessity by policy makers. However, this is not so in the developing nations where rural dwellers and farmers living on farms are neglected or forgotten whenever water supply schemes are being contemplated. This study assessed the impacts of poultry waste dumps on shallow groundwater qualities in twenty poultry farms in Minna, North central Nigeria. Twenty wells were assessed within the twenty farms with respect to their distances from the waste dumps. Water samples were collected from the wells and analyzed. Parameters analyzed were pH, electrical conductivity, total dissolved solids, turbidity, phosphate ion, phosphorus, ammoniacal nitrogen, nitrate nitrogen, nitrite nitrogen, total coliform, faecal coliform and faecal streptococci. Results show that physico-chemical parameters of 60% of the sampled well water except pH and temperature were not within the limit recommended by the World Health Organization (WHO) and Nigerian Drinking Water Quality Standards. Micro-biological parameters of the water samples were also present at elevated values of about 80% of the sampled shallow wells which is an indication of faecal contamination and high probability of disease pathogen in water. Data from the bacteriological analysis of the water samples were regressed with distance between the poultry waste dumps site and the sampled wells. The resulting equations with regression coefficient, R2 of 0.91,0.95 and 0.99 was evaluated to establish the minimum safe lateral distance between poultry waste dumps and the shallow wells in the study area. A minimum distance of 11m was found to be adequate in Minna for zero value of microbiological parameters in the shallow wells. The shallow water table of the area and high hydraulic conductivity of the soil exacerbated the pollution potential from the poultry waste dumps in the farms.